Dynamics of p53 and Wnt cross talk. (December 2015) - Zubbair Malik, Md.; Ali, Shahnawaz; Jahoor Alam, Md.; Ishrat, Romana; Brojen Singh, R.K.
Abstract : Graphical abstract: Abstract : Highlights: The cross-talk between Wnt and p53 signaling pathways allows to regulate each other. Nutlin can able to switch on the somitogenesis at low Axin2 level. Excess Axin2 level in Wnt pathway could trigger the cell to apoptotic phase. Control of one reaction could probably save the cell going from apoptotic phase. Abstract: We present the mechanism of interaction of Wnt network module, which is responsible for periodic somitogenesis, with p 53 regulatory network, which is one of the main regulators of various cellular functions, and switching of various oscillating states by investigating p 53–Wnt model. The variation in Nutlin concentration in p 53 regulating network drives the Wnt network module to different states, stabilized, damped and sustain oscillation states, and even to cycle arrest. Similarly, the change in Axin 2 concentration in Wnt could able to modulate the p 53 dynamics at these states. We then solve the set of coupled ordinary differential equations of the model using quasi steady state approximation. We, further, demonstrate the change of p 53 and GSK 3 interaction rate, due to hypothetical catalytic reaction or external stimuli, can able to regulate the dynamics of the two network modules, and even can control their dynamics to protect the system from cycle arrest (apoptosis).